2012
DOI: 10.1007/s10646-012-0851-1
|View full text |Cite
|
Sign up to set email alerts
|

One-year monitoring of core biomarker and digestive enzyme responses in transplanted zebra mussels (Dreissena polymorpha)

Abstract: A 12-month active biomonitoring study was performed in 2008-2009 on the Vesle river basin (Champagne-Ardenne, France) using the freshwater mussel Dreissena polymorpha as a sentinel species; allochthonous mussels originating from a reference site (Commercy) were exposed at four sites (Bouy, Sept-Saulx, Fismes, Ardre) within the Vesle river basin. Selected core biomarkers (acetylcholinesterase (AChE) activity, glutathione-S transferase (GST) activity, metallothionein concentration), along with digestive enzyme a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 82 publications
(105 reference statements)
1
33
0
Order By: Relevance
“…Micro-PS exposure affected mussels physiology 6.3.1. Modulation of digestion and energy metabolism The induction of glycolysis and digestive activity upon micro-PS exposure may sign increased energy requirements in response to the implementation of anti-oxidant and detoxification processes (Palais et al, 2012). This mechanism would allow the animal to cope with experimental stress and maintain homeostasis, as suggested in a study conducted by Van Cauwenberghe et al (2015) who demonstrated a 25% increase in energy consumption in mussels exposed to micro-PS for 14 days in comparison with controls.…”
Section: Micro-ps Exhibited High Sorption Capacity For Fluoranthenementioning
confidence: 99%
“…Micro-PS exposure affected mussels physiology 6.3.1. Modulation of digestion and energy metabolism The induction of glycolysis and digestive activity upon micro-PS exposure may sign increased energy requirements in response to the implementation of anti-oxidant and detoxification processes (Palais et al, 2012). This mechanism would allow the animal to cope with experimental stress and maintain homeostasis, as suggested in a study conducted by Van Cauwenberghe et al (2015) who demonstrated a 25% increase in energy consumption in mussels exposed to micro-PS for 14 days in comparison with controls.…”
Section: Micro-ps Exhibited High Sorption Capacity For Fluoranthenementioning
confidence: 99%
“…cellulase, glucosidase, and amilase) (Dedourge-Geffard et al, 2009;Palais et al, 2012). For example, changes in these enzymatic responses preceded mortality (b7 days later) in zebra mussels (D. polymorpha) or amphipods (Gammarus fossarum) exposed to metals in laboratory (Dedourge-Geffard et al, 2009) and field conditions (Palais et al, 2012). Also, these enzymatic activities were found to be affected before the target sentinel experienced growth and body condition alterations (Hyne and Maher, 2003).…”
Section: Nonlethal 32%mentioning
confidence: 99%
“…Significant variations in condition index, GST activity and in genotoxicity parameters (MN and SCGE assay) were noted in mussels transplanted downstream compared to upstream. A 12-month ABM performed on the Vesle river basin (France) transplanting D. polymorpha specimens in four sites with different pollution levels pointed out changes in response of AChE, GST, metallothionein, as well as digestive enzyme activities (amylase, endocellulase) and energy reserve concentrations (Palais et al, 2012). According to Smolders et al (2002), all the studies mentioned above highlighted the use of transplanted mussels as a sensitive and easily applicable tool that can be used to assess water quality, pollution and subsequent recovery through selfpurification in field situations.…”
Section: Application Of Biomarkers In Field Studiesmentioning
confidence: 99%